Antibacterial, Antiviral, Antioxidant, and Anticancer Activities of Postbiotics: A review of Mechanisms and Therapeutic Perspectives (Biointerface Research in Applied Chemistry, 2022)
Several scientific evidence has shown the advantageous effects of probiotic-derived metabolites on human health. Postbiotics are a wide range of bioactive compounds derived from probiotics through a fermentation process and/or produced in pure forms in laboratory scales. These compounds have native biological activities that have been extensively studied in recent years. Immunomodulation, antimicrobial, anti-cancer, antioxidant, anti-diabetic, and reduction of food allergies compose the most important biological roles of postbiotics. In terms of safety, it has been confirmed that postbiotics, as potential substitute elements, might be superior to their parent live cells. Also, due to their appropriate economic, technological, and clinical features, they could be employed as favorable apparatuses in the food and drug industry to improve health benefits. This review comprehensively discusses the concept of postbiotics and their characteristics, emphasizing their potential antibacterial, antiviral, antioxidant, and anticancer activities.